Age-related outcomes in patients with cardiogenic shock stratified by etiology - Schmitt, Alexander; Weidner, Kathrin; Rusnak, Jonas; Ruka, Marinela; Egner-Walter, Sascha; Mashayekhi, Kambis; Tajti, Péter; Ayoub, Mohamed; Akın, Ibrahim; Behnes, Michael; Schupp, Tobias (Journal of geriatric cardiology, 2023)
BACKGROUND: As a result of improved and novel treatment strategies, the spectrum of patients with cardiovascular disease is consistently changing. Overall, those patients are typically older and characterized by increased burden with comorbidities. Limited data on the prognostic impact of age in cardiogenic shock (CS) is available. Therefore, this study investigates the prognostic impact of age in patients with CS. METHODS: From 2019 to 2021, consecutive patients with CS of any cause were included. The prognostic value of age (i.e., 60-80 years and > 80 years) was investigated for 30-day all-cause mortality. Spearman’s correlations, Kaplan-Meier analyses, as well as multivariable Cox proportional regression analyses were performed for statistics. Subsequent risk assessment was performed based on the presence or absence of CS related to acute myocardial infarction (AMI). RESULTS: 223 CS patients were included with a median age of 77 years (interquartile range: 69-82 years). No significant difference in 30-day all-cause mortality was observed for both age-groups (54.6% vs. 63.4%, log-rank P = 0.169; HR = 1.273, 95% CI: 0.886-1.831, P = 0.192). In contrast, when analyzing subgroups stratified by CS-etiology, AMI-related CS patients of the group > 80 years showed an increased risk of 30-day all-cause mortality (78.1% vs. 60.0%, log-rank P = 0.032; HR = 1.635, 95% CI: 1.000-2.673, P = 0.050), which was still evident after multivariable adjustment (HR = 2.072, 95% CI: 1.174-3.656, P = 0.012). CONCLUSIONS: Age was not associated with 30-day all-cause mortality in patients with CS of mixed etiology. However, increasing age was shown to be a significant predictor of increased mortality-risk in the subgroup of patients presenting with AMI-CS.